Exploring the Compliance Behaviour During COVID-19 Pandemic from Social Psychology Perspectives - Abdul Rashid, Abdul Aziz; Zuraina, Ali; Najihah, Mohd Noor; Shahirah, Sulaiman (Human Resource Management Academic Research Society (HRMARS), 2021)
The study explores on the compliance behaviour of Malaysians during the pandemic of COVID-19 from the social psychology perspectives. Most of the research materials referred in this study are from secondary resources which are from research articles, newspaper articles, materials from magazines and bulletin. Then, content analysis was employed to obtain relevant themes for the study. Five themes are identified namely, (i) social norms during themCOVID-19 outbreak, (ii) compliance with new norms through social restrictions, (iii) social conformity to adhere to new norms, (iv) optimistic bias during new norms and (v) diffusion of responsibilities during new norms. The implication of the study showed that there are varies compliance and non-compliance behaviours that are demonstrated by fellow Malaysians as the pandemic shows no signs of slowing down. It is therefore vital for Malaysians to follow the appropriate Standard Operation Procedures and be vigilant and resilient in facing this pandemic.